2022
DOI: 10.1021/acsomega.2c04982
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Spectrophotometry of Lignin Revisited: Exploring Solvents with Low Harmfulness, Lignin Purity, Hansen Solubility Parameter, and Determination of Phenolic Hydroxyl Groups

Abstract: In this article, we explored solvents with lower harmfulness than established systems for UV spectrophotometry of lignin. By measuring the absorptivity in DMSO solvent at 280 nm, the purity of the lignin samples was addressed and compared with Klason and acid-soluble lignin. The general trend was an increasing absorptivity with increasing lignin purity; however, considerable scattering was observed around the sample mean. The Hansen solubility parameter (HSP) of four technical lignins was furthermore determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…A platinum Du Noüy Ring was used. Each sample was prepared immediately before the interfacial measurement, as previous results have indicated that aging may affect the sample . The modified lignin was weighed into a volumetric flask and topped up with petroleum distillate, and the mixtures were stirred until complete dissolution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A platinum Du Noüy Ring was used. Each sample was prepared immediately before the interfacial measurement, as previous results have indicated that aging may affect the sample . The modified lignin was weighed into a volumetric flask and topped up with petroleum distillate, and the mixtures were stirred until complete dissolution.…”
Section: Methodsmentioning
confidence: 99%
“…Solubility of lignin in organic solvents is important to process, modify, and utilize this biopolymer. , Technical lignin, such as Kraft, soda, and organosolv lignin, is reportedly soluble in some aprotic polar solvents, such as dimethyl sulfoxide and dimethylformamide, and some protic polar solvents, such as ethylene glycol, ethylene glycol monoethyl ether (“Cellosolve”), 1-methoxy-2-propanol (“Dowanol”), and diethylene glycol monobutyl ether (“Butyl Carbitol”). , Both the extraction process and the biomass origin can have minor effects on the solubility of these lignin types. Lignosulfonates, on the other hand, are highly hydrophilic and are hence reported to be soluble in water, propylene glycol, ethylene glycol, and dimethyl sulfoxide .…”
Section: Introductionmentioning
confidence: 99%
“…The absorbance of the aqueous solution of 5-nitrofurazone was recorded at 375 nm. The average molar solubility of 5-nitrofurazone was calculated from the average absorbance values of eqs 1and . where a is the absorbance value of the dilution solvent, V is the volume of the diluent, W is the dilution factor, and k and b are the slope and intercept of the calibration curve, respectively. m 1 and m i ( I ⩾ 2) represent the mass of 5-nitrofurazone and solvent, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…40 The solubility of lignin macromolecules in appropriate solvents is a critical parameter for effective modication reactions. 42,43 Conventional solvents for lignin include dimethyl sulfoxide (DMSO), toluene, acetone, ethanol, pyridine, methanol, dimethyl formamide (DMF), tetrahydrofuran (THF), chloroform, and dichloromethane. [43][44][45][46] Also, lignin moieties are known to be soluble in hot alkaline solutions.…”
Section: Lignin Functionalization Routesmentioning
confidence: 99%
“…42,43 Conventional solvents for lignin include dimethyl sulfoxide (DMSO), toluene, acetone, ethanol, pyridine, methanol, dimethyl formamide (DMF), tetrahydrofuran (THF), chloroform, and dichloromethane. [43][44][45][46] Also, lignin moieties are known to be soluble in hot alkaline solutions. 44,46,47 Additionally, the solubility of lignin could be further improved by fractionation.…”
Section: Lignin Functionalization Routesmentioning
confidence: 99%